Legal Synchronization Analysis Between Supreme Court Regulation No. 1 of 2019 on E-Litigation and Evidence Provisions in HIR/RBG - MT, Muhammad Zaki Asshafi; Ahmad Irfan Naufal; Muhammad Eric Lionel Prananda (Ilmu Hukum Prima (IHP), 2026)
The digitalization of the judiciary through E-Litigation, as regulated in Supreme Court Regulation No. 1 of 2019, presents challenges in synchronizing with Indonesia’s classical civil procedural law (HIR/RBG), which has been in force for more than a century. This study examines the compatibility between electronic evidence mechanisms under PERMA No. 1 of 2019 and the evidentiary provisions in Article 164 of HIR and Articles 284/285 of RBG. Employing normative legal research with statutory and conceptual approaches, the analysis focuses on vertical and horizontal synchronization. The findings reveal that vertically, PERMA No. 1 of 2019 functions as a gap-filling regeling teknis that expands the interpretation of documentary evidence without contravening higher-level norms. Horizontally, synchronization with the Electronic Information and Transactions Law (ITE Law) provides substantive legitimacy to electronic documents as valid evidence. While procedural unification has been achieved, the main obstacle lies in the legal culture of practitioners who remain attached to paper-based evidence. This study contributes by offering a dogmatic analysis of synchronization—particularly the hierarchical and cultural dimensions—which has been less emphasized in prior studies.